2011
DOI: 10.1097/qad.0b013e32834779df
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics of nevirapine-associated cutaneous and hepatic adverse events among populations of African, Asian, and European descent

Abstract: Objective Nevirapine is widely prescribed for HIV-1 infection. We characterized relationships between nevirapine-associated cutaneous and hepatic adverse events and genetic variants among HIV-infected adults. Design We retrospectively identified cases and controls. Cases experienced symptomatic nevirapine-associated severe (grade III/IV) cutaneous and/or hepatic adverse events within 8 weeks of initiating nevirapine. Controls did not experience adverse events during more than 18 weeks of nevirapine therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(175 citation statements)
references
References 22 publications
7
163
3
2
Order By: Relevance
“…Previous findings have shown that certain HLA types are associated with adverse HAART drug reactions and that these HLA variants do vary in frequency across racial populations. 53,54 Our study has a number of limitations. The MACS is a multiethnic cohort of men only and thus our analysis and conclusions are not directly applicable to dyslipidemic responses in women on HAART.…”
mentioning
confidence: 99%
“…Previous findings have shown that certain HLA types are associated with adverse HAART drug reactions and that these HLA variants do vary in frequency across racial populations. 53,54 Our study has a number of limitations. The MACS is a multiethnic cohort of men only and thus our analysis and conclusions are not directly applicable to dyslipidemic responses in women on HAART.…”
mentioning
confidence: 99%
“…In some studies skin rash has been shown to be related to a CYP2B6516TT polymorphism. 26,27 Rash with NVP has been documented with an overall incidence of 17-32%, although 13% of these are mild rashes. Generally, NVP rashes are transient with risk being greatest in the first 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…NVP shows immunecompetence linked toxicity such that patients with a higher CD4 count and a detectable viral load are seen to be more susceptible to risk of symptomatic hepatic adverse events. 27,36,37 Switching from NVP to EFV in cases of hepatotoxicity has seemed safe and effective. As observed by Walubo et al (2006) 38 , NVP induced hepatotoxicity and liver injury has close association with enzyme induction.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism involved in the development of the adverse events related with NVP is not well understood. Cutaneous effects are most likely MHC class I-mediated, influenced by NVP CYP2B6 metabolism, whereas hepatic toxicity is most likely MHC class IImediated and unaffected by such metabolism [23]. studied so far.…”
Section: Pharmacogenetics Of Nevirapinementioning
confidence: 99%